(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
The availability information about species composition and growth performance of mangrove forest are required to determine the best strategies for sustainable ecosystems management, particularly at the coastal area. This study aimed to quantify the number of species composition and growth performance of mangrove stand that established at the coast of Tanah Merah, East Nusa Tenggara. Forest inventory was conducted using nine permanent sampling plot which evenly distributed in every zonation of mangrove. Data were collected in each life stage of vegetation, namely seedling, sapling, pole, and tree. Several parameters were calculated to describe species composition, including important value index, richness, heterogeneity, and evenness. Four indicators were selected to assess the growth performance of mangrove stand in this location, i.e. mean diameter, average height, timber volume, and wood biomass. Results demonstrated the species composition of mangrove forest consisted of 9 different plants. The highest important value index of seedling was noted in A. marina (124.09) while the greatest important value index of sapling, pole, and tree were recorded in S. alba by approximately 86.57, 130.01, 118.58 respectively. This location had low level of richness (1.22) and heterogeneity (0.88) but having high level of evenness (0.99). The mean diameter and height of mangrove stand in this area was 15.2 cm and 8.3 m with an average timber volume and wood biomass around 90.7 m3 ha-1 and 65.1 Mg ha-1 respectively. Based on these findings, we suggested to conduct enrichment planting for improving plant biodiversity of mangrove forest at the coast of Tanah Merah.